Regulação financeira por objetivos: um modelo regulatório para o futuro? - Melo Filho, Augusto Rodrigues Coutinho de (2018)
The present work intends to investigate the different models of financial regulation, focusing on the model of regulation by objectives or "twin peaks", in the context of the recent transformations in the structure of the global financial market, especially regarding (i) the emergence of new products and services that are not easily framed in a specific segment of the financial market, and can simultaneously develop typical functions of the banking, securities and insurance markets; and (ii) changes in the characteristics of the main participants in this market, among which (ii.1) the unification of financial organizations operating in different sectors of the financial market - investment banks, commercial banks, brokerage firms, insurance companies etc. - resulting in the formation of financial conglomerates; (ii.2) the entry of financial technology companies that compete and provide innovative services in competition with the classic participants of this market. The aforementioned changes should be interpreted as major changes in terms of market structure, and must be observed by regulators in order to assess the compatibility of their respective financial structures with the new risks arising from this "new financial market" in formation. The work is based on the theoretical premise that an efficient and effective regulatory structure needs to reflect the respective market structure that it is intended to regulate, under the risk that such misalignment will result in an empty regulation, without regulatory tools to promote the objectives for which it was created. The hypothesis of this work is that the model of regulation by objectives, as opposed to the unified- and sector-based models, is the most adequate to provide an efficient and effective financial regulation, especially considering that its regulatory structure: (i) enable the fulfillment of multiple objectives of financial regulation in a harmonized manner, in a stage where the complexity of risks emanating from the financial system are increasing, mitigating the possibility of objective overlap within the same agency; and (ii) expand the regulatory perimeters, since the legal criteria for determining the competence of regulators is not linked to concepts of the banking, security and capital sectors, whose distinction increasingly blurred from the point of view that most financial activities have been developed in a cross-sectored way. In order to develop this hypothesis, this dissertation proposes, firstly, to review the theoretical literature on regulation models, with the objective of identifying the characteristics that make a regulatory model “optimal” from the point of view of efficiency and effectiveness. After this analysis, we examine the practical changes happening in the financial market, and how they affect the different regulatory structures in force - propitiating the emergence of the regulation by objectives as the redominant model in some jurisdictions. In this context, regulation by objectives is an option to be considered by the different national regulators to face the new risks of the global financial market and to help the full development of financial markets in the coming decades